Influence of operational sex ratio and male age on mating competition intensity in reindeer (Rangifer tarandus) - Driscoll, Jeffrey G.; Alo, Franco M.; Paoli, Amélie; Weladji, Robert B.; Holand, Øystein; Kumpula, Jouko; Soveri, Timo
2021